Students’ Abilities in Translating Personal Pronouns from Khmer to English - Soy, Seth; Maisarah, Ira (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2022)
Unlike personal pronouns in English, personal pronouns in Khmer do not have the different forms of subject pronouns and object pronouns since a certain word can function both as a subject and as an object of a sentence. Another fact is that the personal pronouns in Khmer have many alternative words for one specific kind of personal pronouns based on the context in terms of age, social position or status, and intimacy. Therefore, the current study aims at investigating students’ abilities in translating personal pronouns from Khmer to English. Specifically, it intends to measure the proportion (percentage) of correct and incorrect translation, and explore types of errors within the translation. The qualitative study employed a set of translation exercises given to 40 students in a class of grade 10 in the first semester of the academic year 2022-2023. To investigate the kinds of errors, the researcher employed the framework of Corder (1974) which categorized errors into 4 types namely error of omission, addition, selection, and error of ordering. The results of the study showed that 82% of exercises were translated correctly. In addition, three types of errors were found. The error of omission was (51%) followed respectively by the error of selection (46%), and the error of addition (3%) but the error of ordering could not be found. The results suggested that the teacher should focus specifically more on the problematic areas of personal pronouns to help the students translate and learn personal pronouns better.